Periprocedural and short-term stroke after transcatheter aortic valve implantation – what are the outcomes and how can we predict it. (14th October 2021) - Castelo, A; Grazina, A; Mendonca, T; Rodrigues, I; Vaz Ferreira, V; Garcia Bras, P; Ramos, R; Fiarresga, A; Cacela, D; Cruz Ferreira, R
Abstract: Background: Stroke is a known complication after transcatheter aortic valve implantation (TAVI). Although risk factors for its occurrence are being suggested, we still don't have clear tools to predict which patients will most probably have it and how to prevent it. Purpose: To identify possible clinical and procedural predictors of early post-TAVI stroke. Methods: Retrospective analysis of consecutive patients (P) submitted to TAVI between 2009 and 2020 in a tertiary center. Baseline characteristics, procedural information and stroke in first 30 days after TAVIwere collected. Results: A total of 494P (56, 1% female) were included, with a mean age of 82±6 years (minimum 45 and maximum 95 years- old). The majority (98, 4%) had at least one cardiovascular risk factor (83, 2% hypertension, 67, 6% dyslipidemia, 64% excess weight, 36, 8% diabetes, 11, 9% smoking). Half patients had chronic kidney disease, 34, 8% atrial fibrillation, 16, 4% peripheral artery disease, 15, 4% porcelain aorta, and 12, 3% a previous stroke. The procedure was done via transfemoral access in 460P (93, 1%), subclavian artery in 16P (3, 2%), transcava in 10P (2%) and transaortic in 7P (1, 4%). Aortic valve pre-dilation was done in 35, 6% and post-dilation in 31, 2%. In the first 30 days after TAVI 19P (3, 8%) had a stroke (11P with a major and 8P with a minor stroke). Patients with stroke had more hypertension (100% vs 82, 4%, p=0.045), higher BMI (29 vs 27, p=0.039) and more frequently porcelain aorta (36, 8% vs 15, 5%, p=0, 014). They also tended to have more peripheral artery disease (31, 6% vs 15, 7%, p=0, 066). There weren't other differences in baseline characteristics between the two groups. Considering the aspects related to the procedure, post-dilation was the only predictor of events (58, 8% vs 32%, p=0, 021). In a multivariable analysis including clinical and procedural predictors, porcelain aorta (p=0, 048, OR = 2, 895) and post-dilation (p=0, 042, OR = 2, 844) were the independent predictors. Stroke after TAVI was associated with longer hospital stay (36 vs 15days, p<0, 001) and intensive care unit stay (12 vs 3 days, p<0, 001), higher intra-hospital mortality (14, 8% vs 3, 2%, p=0, 002), global 30-day mortality (12, 1% vs 3, 3%, p=0, 0011) and cardiovascular 30-day mortality (11, 5% vs 3, 4%, p=0, 038). Conclusion: Periprocedural and 30-day stroke is a relatively uncommon but potentially devastating complication after TAVI. There are clinical and procedural characteristics that are associated with a higher risk and should be considered when selecting patients for treatment and strategies to prevent events. FUNDunding Acknowledgement: Type of funding sources: None.